Pemberdayaan Masyarakat Melalui Hidroponik Sederhana Bagi Masyarakat Rungkut Kidul Kota Surabaya - Erika Aprillia Renata; Savi Nadine Assalma Alhamdany; Ika Sari Tondang (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
This research was conducted by involving the active participation of the Rungkut Kidul community. Through activities to introduce simple hydroponic concepts, communities are empowered to develop sustainable farming skills. The community is given knowledge about the basic principles of hydroponics, nutrient management, selecting suitable plants, and proper irrigation techniques. The results showed that community empowerment through simple hydroponics had a positive impact on the Rungkut Kidul community. Communities are able to independently implement simple hydroponic methods, increase crop production with better yields, and reduce dependence on environmental factors such as rainfall and poor soil quality. In addition, empowerment through simple hydroponics also has a significant socio-economic impact. The Rungkut Kidul community can utilize hydroponic crops for their own consumption needs and as an additional source of income through selling their crops at the local market. This reduces their dependence on external food supplies and boosts the local economy. The introduction of modern agricultural technologies such as simple hydroponics can provide sustainable solutions to increase local food availability, reduce dependence on uncontrollable environmental factors, and improve people's economic well-being.